High performance biobased pour-in-place rigid polyurethane foams from facile prepared castor oil-based polyol: Good compatibility with pentane series blowing agent. (May 2022) - Omrani, Ismail
In this paper, biobased and environmentally friendly rigid polyurethane foams (RPUF) from high hydroxyl value castor oil-based polyols have been prepared without the addition of petroleum-based polyols in the formulation. The new Biopolyol with high hydroxyl value was designed on the basis of the analysis of functionality, structure and hydroxyl value relation and synthesized directly from castor oil in a facile one-pot three-step system. A series of Biopolyols with hydroxyl values in the range of 550–650 mg KOH/g were obtained through transesterification, epoxidation, and hydrolysis. The Biopolyol chemical structure was characterized using FT-IR, 1 H NMR spectroscopies. The formulated blend polyol with amine catalysts and cyclopentane as a blowing agent have good cyclopentane solubility and phase separation between cyclopentane and polyol was not observed after 30 days. The foaming characteristics were evaluated and improved results were obtained. The thermal conductivity, thermal stability, compressive strength, morphology, dimensional stability, density, and foam flow of the RPUFs were characterized. The results are compared with RPUF prepared using standard commercial polyether polyols for pour-in-place RPUFs. The prepared biobased RPUFs from Biopolyol was able to reach the required satisfactory properties for the appliance industry.